2011
DOI: 10.4314/pamj.v8i1.71169
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of nondisclosure of HIV status among women attending the prevention of mother to child transmission programme, Makonde district, Zimbabwe, 2009

Abstract: Introduction The 2007 United Nations General Assembly Report on HIV/AIDS in Zimbabwe reported nondisclosure of HIV status as a challenge in the PMTCT programme. Preliminary investigations on nondisclosure among 21 women tested for HIV at Chinhoyi Hospital showed that only six had disclosed their HIV status. We investigated the determinants of nondisclosure of HIV status. Methods A cross sectional analytic study was conducted at six health facilities in Makonde district.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Second, even with high levels of social support, girls in our study were less likely to discuss their HIV status with others and to feel comfortable disclosing their status, compared to boys. This finding is in line with previous studies in SSA that have documented lower disclosure levels among women-specifically, due to their economic and social vulnerability relative to men, fear of rejection, abandonment or partner violence (63)(64)(65). Although non-disclosure could serve as a protective factor against stigma, it may also have implications for access and utilization of HIV care and treatment among adolescent girls (66).…”
Section: Discussionsupporting
confidence: 90%
“…Second, even with high levels of social support, girls in our study were less likely to discuss their HIV status with others and to feel comfortable disclosing their status, compared to boys. This finding is in line with previous studies in SSA that have documented lower disclosure levels among women-specifically, due to their economic and social vulnerability relative to men, fear of rejection, abandonment or partner violence (63)(64)(65). Although non-disclosure could serve as a protective factor against stigma, it may also have implications for access and utilization of HIV care and treatment among adolescent girls (66).…”
Section: Discussionsupporting
confidence: 90%
“…With the current infant feeding guidelines, HIV-positive women can avoid unwanted disclosure of HIV status and have an identity separate from their disease [ 32 ] and hence avoid the stigma that is associated with the disease or certain disease specific behavior changes required as in old feeding guidelines recommending formula feeding [ 33 ]. A uniform message of EBF to all women regardless of HIV status prevents unwanted disclosure of HIV status and may reduce self-recrimination that HIV positive women feel towards themselves [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, disclosure may help a pregnant HIV-positive woman to take up and adhere to the WHO four pronged approach to PMTCT; which includes 1) safer sex negotiation and behavior change, 2) uptake of contraception to avoid future unwanted pregnancies, 3) uptake of PMTCT preventive strategies such as antiretroviral prophylaxis and EBF, and 4) access to HIV care and treatment for HIV-infected women, their infants, and their families [ 31 , 34 ]. Without disclosure it is difficult for the woman to take medication without being noticed and in a bid to keep her disease private, she may opt out of important PMTCT strategies such as hospital delivery, EBF, contraception, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Females tend to experience more serious consequences of disclosure such as physical and sexual assault [ 11 ]. Furthermore, another study revealed that HIV infected women were two times less likely to disclose their status in fear of abuse, and divorce [ 12 ]. In terms of risk perception, women who perceived greater risk of HIV stigma, were less likely to disclose HIV status to spouse [ 13 ].…”
Section: Introductionmentioning
confidence: 99%